PENGARUH PENINGKATAN PAD DAN DANA TRANSFER TERHADAP BELANJA MODAL DENGAN PERTUMBUHAN EKONOMI SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Kabupaten/Kota di Jawa Tengah Tahun 2016-2021) - Anthony, Aurelia Rayhandita; Rohman, Abdul (Diponegoro Journal of Accounting, 2024)
This research aims to examine the effect of increasing Regional Original Income and Transfer Funds on Capital Expenditures with Economic Growth as a moderating variable. The type of data used is secondary data. The analytical method used to test the hypothesis in this research is Moderated Regression Analysis (MRA) with the SPSS program to test the data.The population used in this research is the 2016-2021 APBD and GRDP Realization report in the Regencies/Cities of Central Java Province which consists of 35 Regencies/Cities. The sample used in this research was 210 dataThe research results show that Regional Original Income and Transfer Funds have a significant effect on Capital Expenditures, however, the Economic Growth variable as a moderating variable is unable to influence Regional Original Income and Transfer Funds on Capital Expenditures